BILANGAN DOMINASI DAN BILANGAN DOMINASI HIPER SEMIGRAF BIPARTIT - Indah Permatasari1 (Jurnal Matematika, 2015)
BILANGAN DOMINASI DAN BILANGAN DOMINASI HIPER SEMIGRAF BIPARTIT Indah Permatasari1, Djuwandi2, Robertus Heri S.U3 Jurusan Matematika FSM Universitas DiponegoroJl. Prof. H. Soedarto, S.H. Tembalang Semarang permatassariindah@gmail.comrobertusutomo@yahoo.co.id ABSTRACT. Semigraph  is a pair  where  is a nonempty set whose elements are called vertices of  and  is a set of ordered n-tuples called edges of . A Semigraph  called bipartite semigraph if its vertex set  can be partitioned into set  such that  and  are independent sets. A set  is a dominating set of  if  adjacent with . If there is not exist  is a dominating set such that  is a minimal dominating set of  and minimum cardinality of a minimal dominating set is called the domination number of   and it is denoted by . A set  is a hyper dominating set of  if  hyper dominated by . If there is not exist  is hyper dominating set such that  is a minimal hyper dominating set of  and minimum cardinality of a minimal hyper dominating set is called the hyper domination number of   and it is denoted by . The study in this thesis that  and  are less than or equal to half of the number of vertices in vertex set . Furthermore, studied application of domination number and hyper domination number for products of selling network in the insurance business.Keywords: semigraph, bipartite semigraph, dominating set, domination number, hyper dominating set, hyper domination number